How many species of Isothecium (Lembophyllaceae, Bryophyta) are there in Macaronesia? A survey using integrative taxonomy. (2nd March 2015) - Draper, Isabel; Hedenäs, Lars; Stech, Michael; Patiño, Jairo; Werner, Olaf; González‐Mancebo, Juana María; Sim‐Sim, Manuela; Lopes, Tina; Ros, Rosa María
<x xml:space="preserve">Abstract</x> Species boundaries are sometimes difficult to assess, especially when molecular data do not neatly match morphologically defined units. This study investigates the moss genus Isothecium, with special emphasis on Macaronesian populations. Morphological studies are combined with the analysis of three rapidly evolving markers: nuclear internal transcribed spacer and plastid trnG and trnL‐trnF. The results of the morphological studies suggest that Isothecium is represented by five species in Macaronesia, including a new endemic species from Madeira, Isothecium montanum sp. nov., which is described here. The molecular results are less conclusive than the morphology results in delimiting species of this genus, even when indels are included as informative. Once possible methodological shortcomings have been discarded, the results can be interpreted as having been caused by incomplete lineage sorting, probably as a consequence of recent speciation. The molecular results also suggest that the origin of the Macaronesian endemics may be explained by at least two independent colonization events. Finally, the delimitation of a new endemic species of Isothecium in Macaronesia indicates that current knowledge on the taxonomy of spore‐producing plants may be far from complete in this hotspot of biodiversity. © 2015 The Linnean Society of London, Botanical Journal of the Linnean Society, 2015, 00, 000–000.